SELECTION OF RECIPIENTS FOR HEART TRANSPLANTATION BASED ON URGENCY STATUS - O. A. Sujayeva; M. I. Davidovitch; S. G. Sudzhaeva; Y. P. Оstrovsky (Вестник трансплантологии и искусственных органов)
The article provides the overview of current international recommendations dedicated to selection of heart transplantation recipients based on urgency status. Authors found that cardiopulmonary bicycle stress test allowed to reveal additional criteria of high death risk within 1 year. These additional criteria were: the maximal oxygen consumption VO2max < 30% of the expected considering the age; VD/VT (ratio of physiologic dead space over tidal volume) increasing during the test; maximal tolerance to physical loading ≤50 Wt and/or < 20% of the expected considering the age. Authors created mathematical model for prediction of death within 1 year based on above mentioned data. Special software estimating the probability of death within 1 year was also created.